La terapia cognitivo conductual y los síntomas negativos en la esquizofrenia - Tania Morales Vigil (Salud Mental, 2015)
Schizophrenia is a health and social problem of great dimensions, affecting not only the patient but their family and social environment. Within the psychotherapeutic approaches for patients with schizo-phrenia, Cognitive Behavioral Therapy (CBT) has most evidence of effectiveness for different porpoises and stages of the disorder.ObjectiveAnalyze the specific techniques and outcome on negative symptoms of the major CBT for patients with schizophrenia: Psychoeducation, Social Skills Training, Cognitive Remediation, CBT for positive symp-toms and Cognitive Behavioral Recovery Oriented Therapy (CBT-R).MethodA searching and analysis of scientific literature published in English and Spanish between 1990 and 2014 were performed in PSYCLIT, MEDLINE, EBSCO-HOST and PROQUEST, employing as key words the names of the different CBT for schizophrenia and the diagnosis. Relevant literature included in review articles was also included.ResultsDespite the advances of CBT, the problems generated by negative symptoms of patients with schizophrenia are not completely solved.Discussion and conclusionCBT-R is considered a promising therapeutic style to achieve the ob-jectives of recovery in patients with low psychosocial functioning and predominance of negative symptomatology.